PENGGUNAAN STRATEGI BELAJAR AKTIF TIPE TRADING PLACE UNTUK MENINGKATKAN AKTIFITAS BELAJAR SISWA PADA MATAPELAJARAN PPKN - Ria Purwasih (JURNAL TEMATIK, 2015)
Abstrak: The low activity of the fourth grade students of SD Negeri 101 777 Saentis in the subject Civics in the subject matter government institutions at the central level. Therefore, this study aims to improve the students' learning activities on the subjects of Civics in the subject matter of Government Institutions in Central Level Elementary School fourth grade Saentis 101 777 FY 2013/2014. This type of research is a classroom action research. Subject of classroom action research conducted in class IV SD, totaling 31 people. Data collection techniques used were observation and questionnaires. This classroom action research consisted of 2 cycles. From the results of this study concluded that the hypothesis that the activity of student learning will increase if the applied active learning strategies trading type place on the subjects of Civics subject matter pemerintaha Institute for Central Level Elementary School fourth grade students 101 777 Saentis TA 2013/2014. Expected to increase activity on civics lesson on the subject matter of government institutions at the central level using active learning strategies trading type place.